INFORMATION АND СULTURAL WAR IN THE CONDITIONS OF ARMED AGGRESSION - Sopilko, Iryna; Cherevatiuk, Viktoriya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: the purpose of the scientific article is to summarize the results of the V International Youth Scientific Legal Forum, during which the issue of information and cultural warfare in the context of armed aggression was discussed. Methods: general and special scientific (special) methods were used to achieve this goal. Results: the authors investigate the essential characteristics of information and cultural aggression against Ukraine. The main threats to the information and cultural security of our state have been identified. The correlation between the development of information policy and information and cultural war in the conditions of armed aggression is shown. Discussion: directions of the state information policy on counteracting information and cultural aggression. Having made its civilizational choice in favor of democracy, our state is using superhuman efforts to curb our neighbor's armed aggression today. Ukrainians are a peaceful people who are forced today to defend their independence, sovereignty, and territorial integrity. Today, Ukraine stands in defense of the whole of Europe, which is the only reason the whole civilized world does not feel all the sufferings of armed aggression. We will persevere because we are driven by the desire for historical justice and faith in the correctness of the chosen path of development. Ukraine is making significant efforts to inform the world community about the crimes of the Russian army, including against Ukrainian culture. It should also be noted that culture is able to return us, Ukrainians, to everyday life in the new military reality and inspire victory. We still have a lot to do. And one of the main principles of our foreign policy should be freedom, one of the categories of which is information freedom - freedom of information, availability of own information space, own sources of information about the world, the subjectivity of own narrative, availability of information channels. The information policy of our state should be aimed at this.